American Culture Transformed - Tucker, B. author. aut Link
XVII, 179 p.
Keywords: The bombing of the Twin Towers in New York on September 11, 2001, marked a major turning point in modern American culture. Authors Bruce Tucker and Priscilla L. Walton examine critical moments in the aftermath of 9/11 arguing that commentators abandoned complexity, seeking to reduce events to their simplest signification.